2008
DOI: 10.1680/gein.2008.15.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lagooned sewage sludge in situ using electrokinetic geosynthetics

Abstract: The treatment and disposal of sewage sludge constitute one of the most problematical issues affecting wastewater treatment in the developed world. Water companies have in the past deposited large volumes of digested sewage sludge in lagoons adjacent to water treatment works, and continue to do so. A lagoon has a potential for causing smell nuisance, represents a major hazard, and frequently occupies a potentially valuable site. Currently no technology exists for treating these lagoons that will both reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…(17) and the non-linear variations of soil properties in Eqs. (4)- (6). In addition, the analytical solution with constant soil properties from Wan and Mitchell [15] is compared with the analytical solution proposed in this study to analyze the effect of the non-linear variations of soil properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17) and the non-linear variations of soil properties in Eqs. (4)- (6). In addition, the analytical solution with constant soil properties from Wan and Mitchell [15] is compared with the analytical solution proposed in this study to analyze the effect of the non-linear variations of soil properties.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment methods have been proposed for the improvement of these soft foundations, among which electro-osmotic consolidation has proven to be a promising method, especially for soils with low permeability [1][2][3][4][5][6][7][8][9][10]. Unlike the traditional methods such as surcharge and vacuum preloading which dewater soil mass by applying a hydraulic gradient, electro-osmotic consolidation involves pairs of anodes and cathodes installed in the soil mass, through which an electrical field is applied and pore water is driven from the anode to cathode under the electrical gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of the exposed conductors can be controlled using oxide coatings. Studies using EVDs have shown the potential for the application of EKG materials in electrokinetic stabilization of soft clays, mine tailings and sludges (Hamir et al 2001;Fourie et al 2007;Glendinning et al 2007Glendinning et al , 2008Rittirong et al 2008). Electro-osmotic consolidation studies using EKG materials as electrodes have been carried out on the soils of Southeast Asia also (Bergado et al 2000(Bergado et al , 2003Chew et al 2004;Lorenzo et al 2004;Lee and Douglas 2007).…”
Section: Electrokinetic Geosynthetics (Ekg)mentioning
confidence: 99%
“…In the 180 V/m test, during first 2 days, water collected at the deformed trough at the surface, some of which drained out through anode end also. In their studies of electrokinetic treatment of sewage sludge, Glendinning et al (2007Glendinning et al ( , 2008 also observed that some water collected around the top of the anodes and cathodes. Due to water recharging at the anode, a closed anode condition is not achieved.…”
Section: Volume Change and Settlement Profilementioning
confidence: 99%
“…Dewatering of sewage sludge using EKG together with a belt press succeeded to raise the dry solids content of the dewatered cake from 19 % to > 30 %, which will make the handling of sludge considerably cheaper [4,5]. Also, the EKG application offers potential to dewater sewage lagoons in situ [6]. Tuan and Sillanpää (2010) combined polyelectrolyte and freeze/thaw conditioning of sludge into an electro-dewatering process, which significantly reduced dewatering time and increased the dry solid content in the final sludge cake [7].…”
mentioning
confidence: 99%